Symposium 4: Early researchers’ experience of a networked learning forum: A site of learning and challenges - Cutajar, Maria; Calleja, James (Proceedings of the International Conference on Networked Learning, 2024)
International conferences and fora bringing together a diverse group of researchers, scholars and practitioners are claimed to be sites of learning and networking. This paper reports on the findings of an explorative study investigating the experience of early researchers participating in the Networked Learning Forum 2021 which was specifically planned to support their learning and development. These qualitative findings are part of the encompassing evaluation study of the event more generally. This part study implemented thematic analysis on transcript data of a focus-group interview held with participating early researchers soon after the end of the event. In this paper, we share the thematic description of the early researcher’s experience as emerged from this group interview. This description generally confirms the preliminary survey findings showing up the Networked Learning Forum 2021 as a site of learning and development. But distinctively, in this part of the study, the event surfaced as a site of early researcher challenges. ‘Learning experience’ came to the fore as a strong core theme configured by 4 primary, constituent themes; ‘event organisation’, ‘interactions’, ‘means of acquisition’ and ‘researcher challenges’. Each of these 4 primary themes was structured by a number of subthemes. This thematic description of the Networked Learning Forum 2021 experience from the perspective of participating early researchers, highlights the event as a compelling, participatory event bearing substantial academic advantage for learning and development. Distinctively, the academic advantage emerges as closely linked to what are identified as researcher challenges. This thematic picture, based on a single case, is very limited in scope. Further research is needed to verify claims. But meanwhile it is reasonable to listen to the recommendations made by the early researchers of this study encouraging similar events. Such events make it easier for beginning researchers to connect with experts and international peers. They facilitate beginning researchers to present their research to an international audience within a relatively less intimidating environment compared to typical international conferences which are much larger. They provide a space for beginning researchers to be challenged in developing research related competences and emotionally grow as researchers.